2017
DOI: 10.1186/s10194-017-0802-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-life use of onabotulinumtoxinA for symptom relief in patients with chronic migraine: REPOSE study methodology and baseline data

Abstract: BackgroundMigraine is a debilitating neurological disorder that affects 14.1% of the US and 14.7% of the European populations. Chronic migraine (CM) is broadly defined as headache occurring on ≥15 days per month for ≥3 months, and has an estimated worldwide prevalence of 1.4% to 2.2%. OnabotulinumtoxinA is currently approved for the treatment of CM in most European countries, and is the only preventative treatment approved for adults with CM, based on results from the PREEMPT clinical trial programme. The ongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
1
16
0
1
Order By: Relevance
“…Since PREEMPT regulatory trials were done, several open‐label and real‐life pragmatic studies have already demonstrated the effectiveness of onabotulinumtoxinA in terms of frequency and analgesic intake as main end‐points but also in improving headache intensity and quality of life .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PREEMPT regulatory trials were done, several open‐label and real‐life pragmatic studies have already demonstrated the effectiveness of onabotulinumtoxinA in terms of frequency and analgesic intake as main end‐points but also in improving headache intensity and quality of life .…”
Section: Discussionmentioning
confidence: 99%
“…OnabotulinumtoxinA is currently approved as a preventative treatment for CM in the USA and most European countries, including Spain , based on results of the PREEMPT clinical trial programme . Since then, consensus guidelines and a large number of real‐life clinical studies have been published with findings on clinical predictors of response , comparison to other current preventative treatments and endorsing its effectiveness and safety in different long‐term cohorts .…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation from drug abuse, in whichever modality it is carried out, produces de facto a return to CM [ 7 ]. The same therapies applied today to CM are in fact efficacious with or without the presence of MOH, and an artificial distinction of a classification does not distinguish their efficacy [ 8 10 ].…”
Section: Medication Overuse Headache: Chasing Roots and Bordersmentioning
confidence: 99%
“…International, multicentre, open-label long-term prospective study COMPEL (The Chronic Migraine OnabotulinumtoxinA Prolonged Efficacy open Label) provided additional clinical evidence of efficacy and long-term safety and tolerability [ 22 ]. European, open-label, multicentre, prospective, noninterventional study REPOSE provided evidence of a sustained reduction in headache-day frequency and significant improvements in QoL in CM patients treated with Botox [ 23 ].…”
Section: Introductionmentioning
confidence: 99%